Возможная архитектура системы хранения данных достижений студента университета на основе технологии blockchain - Мартышкин, А. И. (Видавництво НТУ «ДП», 2019)
В статье проводится результат исследования применимости технологии Blockchain для реализации распределенных реестров личных данных, на примере реестра достижений студента университета. Рассматривается организация взаимодействия в системе. Приводится выражение для расчета Хэша транзакции.

The article presents the result of a study of the applicability of the Blockchain technology for the implementation of distributed registries of personal data, based on the example of the university student achievement register. The organization of interaction in the system is considered. An expression is provided to calculate the transaction hash.
Possible architecture of the storage system of data of the achievements of the student of the university based on blockchain technology
Keywords: распределенные системы; блокчейн; криптовалюта; информационные технологии; реестр; токен; хэш‐идентификатор; distributed systems; blockchain; cryptocurrency; information technology; registry; token; hash identifier